2022
DOI: 10.3390/plants11192448
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Fungi Mediated Alleviation of Drought Stress via Non-Enzymatic Antioxidants: A Meta-Analysis

Abstract: Drought stress constrains plant cell metabolism and induces the production of reactive oxygen species (ROS). In response to drought stress, plants induce a series of physiological and biochemical changes, scavenging ROS. Among soil microbes, arbuscular mycorrhizal fungi (AMF) are found to be effective ameliorators of ROS under drought-stress conditions. However, the comprehensive roles of the oxidative stress ameliorators mediated by AMF in alleviating drought stress are not studied in detail. The present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…Hu et al [53] also reported that mycorrhizal plants had lower levels of malondialdehyde than non-mycorrhizal plants, which is in line with our data. In agreement are also, the results of Chandrasekaran [54] which clearly showed that AMF inoculation decreased the level of H2O2, which, in turn, reduced lipid peroxidation by MDA content and membrane stability by the reduced level of EL. Moreover, AMF plants induced high levels of carotenoids, which enhanced their soluble sugars and ABA levels better and faster than non-AM plants.…”
Section: Discussionsupporting
confidence: 87%
“…Hu et al [53] also reported that mycorrhizal plants had lower levels of malondialdehyde than non-mycorrhizal plants, which is in line with our data. In agreement are also, the results of Chandrasekaran [54] which clearly showed that AMF inoculation decreased the level of H2O2, which, in turn, reduced lipid peroxidation by MDA content and membrane stability by the reduced level of EL. Moreover, AMF plants induced high levels of carotenoids, which enhanced their soluble sugars and ABA levels better and faster than non-AM plants.…”
Section: Discussionsupporting
confidence: 87%
“…Regarding the carotenoid concentrations, for the VR808 genotype, the concentration levels tended to decrease by 86.8% and 84.4% in the NM and MIX treatments, respectively, under the S2 drought level compared to those in the same inoculation treatment without stress (S0). In contrast, meta-analyses have shown that concentrations increase with inoculation and the application of water stress and that the percentage of this increase depends on the level of stress applied [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…As functions of symbiosis of mycorrhizal fungi (Chandrasekaran, 2022;Begum et al, 2023;Zou et al, 2023), plant growth-promoting rhizobacteria (PGPR) (Shankar and Prasad, 2023;Tanveer et al, 2023;Zhao et al, 2023), and dark septate endophytes (DSE) (Li et al, 2022;He C. et al, 2022;Liu et al, 2023) during drought stress, root endophytic fungi also play important roles in increasing tolerance to drought stress of their host plants (Azevedo et al, 2021;Manzur et al, 2022;Zuo et al, 2022). S. indica is also a root endophytic fungus, and it improves drought tolerance of their host plants, as described above.…”
Section: Discussionmentioning
confidence: 99%